2006
DOI: 10.1055/s-2006-939696
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Copper Iodide Catalyzed Phosphorus-Carbon Bond Formation: An Efficient Synthesis of Scalemic Tertiary Phosphineboranes

Abstract: A mild and efficient protocol for P-C bond formation was developed with sub-stoichiometric amounts of copper iodide as a catalyst. A series of sterically and electronically divergent phosphineboranes were subjected to coupling reactions and the corresponding products were obtained in high yields with retention of configuration. The reaction proceeded under non-basic conditions thus avoiding base-catalyzed racemization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The reduction of the P=O bond with BH3 is possible due to the intramolecular complexation of P=O•B coordinated by α-or β-hydroxy groups present in the phosphine oxide structure. The conversion of hydroxyalkylphosphine oxides to hydroxyalkylphosphine boranes were obtained with a full inversion of the configuration at phosphorus [164,[166][167][168][169]. It was found that the P-alkylation reaction proceeds with good yield and high enantiospecificity (ee > 95%) with various alkyl halides.…”
Section: Addition To Multiple Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of the P=O bond with BH3 is possible due to the intramolecular complexation of P=O•B coordinated by α-or β-hydroxy groups present in the phosphine oxide structure. The conversion of hydroxyalkylphosphine oxides to hydroxyalkylphosphine boranes were obtained with a full inversion of the configuration at phosphorus [164,[166][167][168][169]. It was found that the P-alkylation reaction proceeds with good yield and high enantiospecificity (ee > 95%) with various alkyl halides.…”
Section: Addition To Multiple Bondsmentioning
confidence: 99%
“…Chiral phosphine boranes obtained from adamantylphosphinates are of interest as synthetic blocks (Equations (117) and (118)) [138]. (116) (117) (118) An alternative method for the synthesis of P-stereogenic adamantyl phosphinates is based on the introduction of a hydroxymethyl group into phosphinates to control the stereoselectivity of the subsequent reduction by borane-THF complex [167][168][169]. The reaction of adamantylphosphinates with formaldehyde led to the formation of optically pure hydroxymethylphosphinates (Equation (119)).…”
Section: Addition To Multiple Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…When PHPh(t-Bu)(BH 3 ) of 99% ee was used, the reaction proceeded with retention of configuration at phosphorus (Scheme 36); other chiral phosphine-boranes behaved similarly [58]. …”
Section: Activation Of An Unsaturated Electrophilementioning
confidence: 99%
“…Cu-catalysed reaction of ethyl diazoacetate and enantiopure secondary phosphine borane produces enantiopure tertiary phosphine-borane complex in good yields. [185] P-chiral phosphine and diphosphine species can also be synthesised via Pt-and Ru-catalysed enantioselective coupling of racemic secondary phosphines with alkyl bromides and chlorides respectively (Scheme 1.51 and 1.52). [186][187] Scheme 1.51 Pt-catalysed asymmetric alkylation of secondary phosphines.…”
Section: General Metal-catalysed C-x/p-y Cross-couplingsmentioning
confidence: 99%